Karyological reports for some Salvia taxa from Turkey - Kursat, Murat; Emre, Irfan; Gedik, Osman; Kiran, Yasar (Firenze Univ Press, 2018)
The aim of this study is to determine of the some karyological properties and chromosome numbers of eight Salvia taxa (S. euphratica var. euphratica, S. euphratica var. leicalycina, S. hypargeia, S. candidissima subsp. candidissima, S. frig ida, S. virgata, S. suffruticosa, and S. verticillata subsp. verticillata) from Turkey. The ploidy levels, karyotype formula, chromosome length range, total karyotype length, several karyotype asymmetry values, Stebbins classification and the A1 and A2 were a determined in this study. Also, Pearson correlations between the karyotype asymmetries of the Salvia taxa were calculated and dispersion diagram was formed. It was determined that the Salvia taxa had 2n = 14, 18, 22 and 32. The basic chromosome number of x = 7 may be regarded as primary, the others (x = 9, 11, 16) are estimated to be secondary basis. Based on Stebbins classification, it was found that S. euphratica subsp. euphratica was 1A, S. hypergeia and S. suffruticosa were 3A and the other taxa were 2A. The taxa had median point (M), median (m), submedian (sm), subterminal (st) chromosomes. There were no observed satellites and B chromosomes in the studied taxa.
Keywords: Lamiaceae; chromosome number; Salvia; karyotype; Turkey